Leading change: dilemmas, challenges and lessons learned - Andersen, Lotte Bøgh; Bøllingtoft, Anne; Christensen, Martin; Hald, Ida Bøgh (Politica, 2016)
How can public managers implement organizational change in organizations with very different users? This article presents and illustrates key insights from the change management literature, the literature on employee motivation and user capacity literature and the sociology of professions. The empirical case is a merger between two schools in Denmark. The theory expects public managers to be able to influence whether the changes are seen as transformational or incremental and to choose between proactive and reactive actions. Especially if they act proactively, a shared vision is expected to be important, but it can be challenging to secure ownership of this vision for professional employees with high public service motivation. The theory also expects that the establishment of common rules is challenging, when we are looking at changes involving very different users and in organizations with different cultures. All these theoretical insights are illustrated for a specific merger of two primary and lower secondary Danish schools.